PEMBATASAN KEWENANGAN HAKIM UNTUK TIDAK MELAKUKAN SITA JAMINAN ATAS SAHAM DIKAITKAN DENGAN BUKU PEDOMAN TEKNIS ADMINISTRASI DAN TEKNIS PERDATA UMUM (Jurnal Hukum Mimbar Justitia, 2017)
ABSTRACTA Judge is a legal authorized profession to hear cases in court. In deciding cases aJudge always use the rampage: "For the sake of Justice based on the One Godhead".One of the most important things that people analyze about the judge is the behavior ofthe judges, whether in performing their judicial duties or in their daily activities. Inaccordance with the duties and authorities, the judge is to be required to maintain anduphold their honor, dignity, and ethics and behavior. The Judges must obey the Supreme Court of the Republic of Indonesia Number KMA / 032 / SK / IV / 2006 AboutGuidelines book II on the Implementation of Duties and Administrative Courts, 2007edition, which subsequently revised in 2009. Inside the book, there are generaltechnical administrative and technical civil guidelines, Especially concerning thejudiciary in the Y letter, namely the confiscation of the defendant's property(conservatoir beslag) on number 11 stated that judge does not seize the collateral forthe shares and number 12 blocking of shares is done by Bapepam/ now OJK by therequest of the President of the Court, in case there must be a relationship, Thus, thejudge has limit authority. So that, it is difficult for judges to stocks grant confiscation.Keywords: Judge; Authority to Prosecute; Justice; stocks grant confiscation; GeneralTechnical and Administrative Technical Guidelines.